Upadacitinib as monotherapy and in combination with non-biologic disease-modifying antirheumatic drugs for psoriatic arthritis. (3rd December 2021) - Nash, Peter; Richette, Pascal; Gossec, Laure; Marchesoni, Antonio; Ritchlin, Christopher; Kato, Koji; McDearmon-Blondell, Erin L; Lesser, Elizabeth; McCaskill, Reva; Feng, Dai; Anderson, Jaclyn K; Ruderman, Eric M
Abstract: Objective: To assess the efficacy and safety of upadacitinib (UPA), an oral Janus kinase inhibitor, as monotherapy or in combination with non-biologic DMARDs (nbDMARDs) in patients with PsA. Methods: Pooled data were analysed from patients with prior inadequate response or intolerance to one or more nbDMARD (SELECT-PsA 1) or one or more biologic DMARD (SELECT-PsA 2) who received placebo, UPA 15 mg once daily (QD) or UPA 30 mg QD as monotherapy or in combination with two or fewer nbDMARDs for 24 weeks. Efficacy outcomes included achievement of ACR responses, Psoriasis Area and Severity Index responses, minimal disease activity and change from baseline and clinically meaningful improvement in the HAQ Disability Index. Adverse events (AEs) were summarized. Results: A total of 1916 patients were included; 574 (30%) received monotherapy and 1342 (70%) received combination therapy. Placebo-subtracted treatment effects for a 20% improvement in ACR criteria at week 12 were 33.7% (95% CI 24.4, 43.1) and 34.0% (95% CI 27.9, 40.1) for UPA 15 mg QD monotherapy and combination therapy, respectively, and 45.7% (95% CI 36.9, 54.5) and 39.6% (95% CI 33.7, 45.5) for UPA 30 mg QD monotherapy and combination therapy, respectively. Treatment effects for other outcomes were consistent between monotherapy and combination therapy. AE frequency was generally similar for UPA monotherapy and combination therapy, although hepatic disorders and creatine phosphokinase elevation were more common with combination therapy vs monotherapy. Conclusion: The efficacy and safety of UPA were generally consistent when administered as monotherapy or in combination with nbDMARDs through 24 weeks, supporting the use of UPA with or without nbDMARDs in PsA. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov ): SELECT-PsA 1 (NCT03104400), SELECT-PsA 2 (NCT03104374)